2003
DOI: 10.1093/jn/133.2.468
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan Fractions from Barley and Oats Are Similarly Antiatherogenic in Hypercholesterolemic Syrian Golden Hamsters

Abstract: The cholesterol-lowering activities of oats and barley are commonly attributed to the beta-glucan fractions. Although beta-glucan is present in both grains and appears to be chemically similar, the effect of source on cholesterol-lowering activity has not been evaluated. In the present study, the antiatherogenic properties of beta-glucan concentrates from oats and barley were evaluated in Syrian golden F(1)B hamsters consuming a semipurified hypercholesterolemic diet (HCD) containing cholesterol (0.15 g/100 g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
2
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 46 publications
4
114
2
3
Order By: Relevance
“…Plasma and urine creatinine concentrations were measured, using HPLC (Beckman Instruments, Fullerton, CA, USA). The kidney lipids were extracted using the method of Bligh and Dyer with slight modifications, as previously described [22].…”
Section: Methodsmentioning
confidence: 99%
“…Plasma and urine creatinine concentrations were measured, using HPLC (Beckman Instruments, Fullerton, CA, USA). The kidney lipids were extracted using the method of Bligh and Dyer with slight modifications, as previously described [22].…”
Section: Methodsmentioning
confidence: 99%
“…Since control diets and diets with a 40% share of naked oat contained similar levels of crude fibre, the obtained results could have been affected by a different content of soluble dietary fiber, including soluble β-glucan. According to Delaney et al (2003), not only oat β-glucan, but also barley β-glucan is antiatherogenic. However, assuming a β-glucan content of 3.6% in barley and oat grains, and of 1% in triticale grains (Bach Knudsen, 1997), the administered oat diets had an approximately 45% higher β-glucan content than control diets (21.7 vs 14.8 g .…”
Section: Discussionmentioning
confidence: 99%
“…2). Many studies with monogastric animals, including humans, have demonstrated reduction in the levels of serum cholesterol and cholesterol-related composts with the use of fibrous diets (Ludwig et al, 1999), and the most efficient reducer was the soluble fibers (Delaney et al, 2003). One of the hypotheses for this effect is the capacity of some fiber constituents for adsorbing the steroids and derived composts, including bile salts and cholesterol, which are excreted through faeces.…”
Section: Trialmentioning
confidence: 99%